Karl Marx: Manifesto, Radical Democracy Or Futuristic Alchemy - Šutović, Milojica M. (Sociološki pregled, 2018)
The celebration of 200th anniversary of birth of Karl Marx, a renowned social theorist and the symbol of world revolution, not less an intellectual, as well as 170 years since publication of the Manifesto of the Communist Party, the foundation and the ideological programme of the liberation from capitalism movement, seems to bring Marx back into the heart of capitalism, extreme and arrogant liberalism. That is done in commercial, marketing and tourist way, turning him into a souvenir and “the goods” of social system without an alternative, for which the term capitalism itself is dispensable. That way even Marx’s criticism of capitalism is pacifed through a kind of normalization of explosive potential, its contradictions (exploitation, poverty, inequality), reducing his deepest and the most mature analytic consideration of the structure of capitalist relations to a conservative implication. Such implication is more due to Marx’s personality than the coherence of his writings, especially the Manifesto of the Communist Party, in which the frst step towards the inescapable “futuristic alchemy” of the communist revolution, i.e. “proletariat organized into a ruling class”, is a struggle for democracy. Paradoxically as it may sound, it even brought about the crash of communism, the unfnished vision of free society that is in the core of Marx’s Manifesto. The question remains whether that vision would forever stay buried under these ruins or the necessity of its excavation would make Marx’s ideas and work topical again.Keywords: Marx, Manifesto, democracy, communism, futuristic alchemy.